Hypotensive Response to Angiotensin II Type 2 Receptor Stimulation in the Rostral Ventrolateral Medulla Requires Functional GABA-A Receptors - Légat, Laura; Brouwers, Sofie; Smolders, Ilse J.; Dupont, Alain G. (Frontiers in Neuroscience, 2017)
Objectives: Angiotensin II, glutamate and gamma-aminobutyric acid (GABA) interact within the rostral ventrolateral medulla and the paraventricular nucleus modulating the central regulation of blood pressure and sympathetic tone. Our aim was to assess the effects of local angiotensin II type 2 receptor stimulation within the rostral ventrolateral medulla and the paraventricular nucleus on neurotransmitter concentrations and mean arterial pressure. Methods: In vivo microdialysis was used for measurement of extracellular glutamate and GABA levels and for local infusion of the angiotensin II type 2 receptor agonist Compound 21 in the rostral ventrolateral medulla and the paraventricular nucleus of conscious normotensive Wistar rats. The mean arterial pressure response to local Compound 21 was monitored with a pressure transducer under anaesthesia. Angiotensin II type 2 receptor selectivity was assessed using the angiotensin II type 2 receptor antagonist PD123319; the GABA-A receptor antagonist bicuculline was used to assess the involvement of GABA-A receptors. Results: Infusion of C21 (0.05µg/µl/h) in the rostral ventrolateral medulla significantly increased GABA levels and lowered blood pressure. These effects were abolished by co-infusion with PD123319. No changes in neurotransmitter levels or effects on blood pressure were seen with PD123319 infusion alone. Co-infusion of bicuculline abolished the Compound 21 evoked decrease in mean arterial pressure. Infusion of Compound 21 within the paraventricular nucleus did not change extracellular neurotransmitter levels nor mean arterial pressure. Conclusion: Selective stimulation of angiotensin II type 2 receptor within the rostral ventrolateral medulla by local Compound 21 infusion reduces blood pressure and increases local GABA levels in normotensive rats. This hypotensive response requires functional GABA-A receptors, suggesting that GABAergic neurons are involved in the sympatho-inhibitory action underlying this hypotensive response.